Reduction of endogenous transforming growth factors β prevents ontogenetic neuron death - Krieglstein, Kerstin; Farkas, Lilla; Dünker, Nicole; Unsicker, Klaus (Nature neuroscience, 2000)
We show that following immunoneutralization of endogenous transforming growth factors (TGF-) in the chick embryo, ontogenetic neuron death of ciliary, dorsal root and spinal motor neurons was largely prevented, and neuron losses following limb bud ablation were greatly reduced. Likewise, preventing TGF- signaling by treatment with a TR-II fusion protein during the period of ontogenetic cell death in the ciliary ganglion rescued all neurons that normally die. TUNEL staining revealed decreased numbers of apoptotic cells following antibody treatment. Exogenous TGF- rescued the TGF--deprived phenotype. We conclude that TGF- is critical in regulating ontogenetic neuron death as well as cell death following neuronal target deprivation.